Social Well-Being and Aggressiveness to Employees : Kesejahteraan Sosial dan Agresivitas pada Karyawan - Nila Permata Febri Arinta; Effy Wardati Maryam (Academia Open, 2022)
This study explores the relationship between social welfare and employee aggressiveness, focusing on oppressive, threatening, and intimidating behaviors that create discomfort among employees. Employing a quantitative approach with correlation analysis, a sample of 100 employees was obtained using a non-probability sampling technique. The social welfare scale, adapted from Keyes, yielded a Cronbach's alpha of 0.952, while the aggressiveness scale, adapted from Ubaidillah, achieved a Cronbach's alpha of 0.926. The findings reveal a significant negative relationship between social welfare and employee aggressiveness. Pearson's product-moment correlation demonstrated a significance of 0.002, indicating that higher levels of social welfare are associated with reduced employee aggressiveness. These results hold implications for organizations seeking to foster positive work environments and mitigate aggressive behaviors, thereby enhancing overall employee well-being and productivity. Highlights: Relationship between social welfare and employee aggressiveness: This study examines the connection between social welfare and employee aggressiveness, focusing on oppressive behaviors and their impact on employee well-being. Quantitative approach and correlation analysis: The research utilizes a quantitative approach, employing correlation analysis to analyze the data collected from a sample of 100 employees. Importance of positive work environment: The findings highlight the significance of fostering a positive work environment to reduce employee aggressiveness and enhance overall well-being, ultimately leading to improved productivity. Keywords: Social welfare, employee aggressiveness, quantitative approach, correlation analysis, positive work environment.